A Comparative Analysis of Ethnomedicinal Practices for Treating Gastrointestinal Disorders Used by Communities Living in Three National Parks (Korea). (14th August 2014) - Kim, Hyun; Song, Mi-Jang; Brian, Heldenbrand; Choi, Kyoungho
Abstract : The purpose of this study is to comparatively analyze the ethnomedicinal practices on gastrointestinal disorders within communities in Jirisan National Park, Gayasan National Park, and Hallasan National Park of Korea. Data was collected through participant observations and indepth interviews with semistructured questionnaires. Methods for comparative analysis were accomplished using the informant consensus factor, fidelity level, and internetwork analysis. A total of 490 ethnomedicinal practices recorded from the communities were classified into 110 families, 176 genera, and 220 species that included plants, animals, fungi, and alga. The informant consensus factor values in the disorder categories were enteritis, and gastralgia (1.0), followed by indigestion (0.94), constipation (0.93), and abdominal pain and gastroenteric trouble (0.92). In terms of fidelity levels, 71 plant species showed fidelity levels of 100%. The internetwork analysis between disorders and all medicinal species are grouped in the center by the four categories of indigestion, diarrhea, abdominal pain, and gastroenteric trouble, respectively. Regarding the research method of this study, the comparative analysis methods will contribute to the availability of orally transmitted ethnomedicinal knowledge. Among the methods of analysis, the use of internetwork analysis as a tool for analysis in this study provides imperative internetwork maps between gastrointestinal disorders and medicinal species.